Alternate Week Gemcitabine and Capecitabine: An Effective Treatment for Patients With Pancreatic Adenocarcinoma. Issue 7 (August 2019) - Johns, Claire; Diaz, Celso L.; Hwang, Jimmy; Kerridge, William D.; Ko, Andrew H.; Tempero, Margaret A.
Abstract : Objective: Determine whether a regimen of fixed dose rate gemcitabine plus capecitabine is effective and tolerable for advanced pancreatic adenocarcinoma. Methods: We performed a retrospective analysis of 62 patients with locally advanced or metastatic pancreatic adenocarcinoma treated at the University of California San Francisco between 2008 and 2016. Treatment was an alternate week schedule of fixed dose rate 1000 mg/m 2 gemcitabine and capecitabine 1000 mg/m 3 (58 patients), 1200 mg/m 3 (12 patients), or 650 mg/m 3 (1 patient) for intended 12 cycles. We evaluated overall survival (OS), progression-free survival (PFS), radiologic response, and adverse events necessitating treatment modification. Results: For metastatic patients, median OS was 10.3 months (95% confidence interval [CI], 6.7–12.1 months), and PFS was 5.6 months (95% CI, 2.6–7.7 months). In locally advanced patients, OS was 12.0 months (95% CI, 4.9–17.1 months), and PFS was 5.4 months (95% CI, 2.5–9.4 months). Radiologic response for metastatic disease (42 patients) was 19% objective response, 45% stable disease, and 36% progressive disease. Treatment required modification for 22 patients due to adverse events, most frequently hand-foot syndrome (18 patients). Conclusions: Alternate week schedule of fixed dose rate gemcitabine and capecitabine was active and tolerable for advanced pancreatic adenocarcinoma. Overall survival and PFS were comparable to first-line treatments. Importantly, adverse effects appear less severe than first-line treatments.